Entrepreneurial Imaginativeness in New Venture Ideation - Kier, Alexander S.; McMullen, Jeffery S. (Academy of Management Journal, 2018)
Although theories of entrepreneurial action regularly acknowledge the importance of imagination, the ability is rarely defined or measured, and thus effectively treated as uniform in degree and type. Using a creative problem-solving lens, we identify and measure three different cognitive skills—creative, social, and practical imaginativeness—that vary across individuals. Each skill combines the ability of imagination with the knowledge needed to mentally simulate various task-related scenarios used in generating and selecting ideas for new value creation. We then conduct a quasi-experiment to examine each skill’s relative effect on new venture ideation. We find that the three imaginativeness skills vary across individuals and that they predict new venture idea quantity and quality differently over and above the effects of motivation, knowledge, and experience. We conclude with implications for theory development in entrepreneurship and creative problem-solving.